(untitled) (Revista Argentina de Musicología, 2020)
During the period of “cultural emancipation” (1884-1930), European impresarios fulfilled a relevant and controversial role in the development of the performing arts in South America. Often connected to each other through underhanded agreements, they ruled the transatlantic infrastructure and thus led the market, conveying the offer and developing the cultural demand, as result of shifting political, economic and migratory dynamics. Although the importance of these entrepreneurs was clear at the time - and often emphasised or praised by politics, intellectuals and competitors - the role of the European impresario in South American theatrical market still needs to by explored in a broad perspective. This paper aims to contribute to the understanding of this crucial figure in the development of the arts through the perspective of some of the leading impresarios whose business flourished in Buenos Aires, undisputable cultural capital of the belle époque. Set at the centre of the transatlantic musical trade, in the early 1900s the metropolis became the most important market for the musical exportation of Italian and French composers, in the same period in which the ’Argentine centennial’ brought about a deep change in the attitude towards the European models